Numerical investigation of airflow in a swirling fluidized bed - Batcha, Mohd Faizal Mohideen; Mohd Nawi, Mohd Al-Hafiz; Sulaiman, Shaharin Anwar (2013)
A numerical investigation via commercial Computational Fluid Dynamic (CFD) package, FLUENT, was carried out to investigate the aerodynamic characteristics of air flow in a Swirling Fluidized Bed (SFB). The study focused on the distributor blade configurations whereby the effect of number of blades and blade inclination in radial plane were investigated. Twelve configurations were simulated at 30, 45 and 60 blades for four radial inclinations, 0, 10, 13.5 and 15°. Two criterions were taken as performance characteristics to evaluate each configuration namely the uniformity of tangential velocity distribution and pressure drop. High uniformity at the distributor outlet will ensure uniform solid-gas contact in the actual system while low pressure drop is vital to minimize power consumption in the system. From the results, it was evident that the 30 blades with 10E radial inclination of distributor blade in plenum chamber offer the best configuration for actual application.